PROBABILITAS BANGKITAN PERJALANAN BERBASIS AKTIVITAS DARI KAWASAN PERUMAHAN DI KOTA KUPANG - Semiun, Oktovianus Edvict; Kalogo, Egidius (Teras Jurnal : Jurnal Teknik Sipil, 2020)
Generally, trip generation is based on activities from the household. Each household member, of course, has different travel destinations in a household, there will be several trips that are caused by the activity. This study is aimed at determining the factors that influence the trip generation and predict the magnitude of trip generation originating from residential areas based on activities in Kupang city. Travel activities were divided into three categories i.e. work activities, school activities and other activities. Data collection was done by distributing questionnaires to 444 households through random sampling technique. Based on the calibration of the modelling results with multinomial logit regression analysis, the factors that significantly influence trip generation from residential areas were the number of family members who did activities, the average distance travelled and the average travel time. The probability of trip generation was predicted to be 55.48% for work activities, 25.61% for school activities and 18.90% for other activities.